PERANCANGAN DESAIN PRODUK BUSANA PANTAI BRAND PARUMPUDICI UNTUK WANITA PLUS SIZE - Pradnyaswari, Putu Dyah; Soelistyowati, - (Jurnal VICIDI, 2020)
This design is made in regards to the establishment of the fashion brand "Parumpudici" for plus size woman , by taking a sample of Parumpudici’s targeting market in Bali . This is a solution for the problems that was encountered by Plus Size woman in bali to find a suitable beach wear products for themselves .The design progress is made based on the result of qualitative data base research and interviewing the expert and the extreme users, which then adjusted with the trend, body type and the needs of plus size woman. The production process consist of some steps design the mood board, product design, pattern, the selections of the material, making the sample, revision, final sewing . The theme of the collection is "Blush Lagoon” in which the focus of the design is on the manipulation technique color blocking, lines, cutting and the additional decorative application such as fringe that show the body shape and the proper balance of the plus size woman’s body. The colors that are used pastel color which inspired by soft colors of sea under water like oceanic green, soft blue, soft pink and sands color. Solid color like black is consistently used to give the impression of firm and elegant.